Influence of Work Facilities and Cross-Cultural Communication on the Performance of Back Office Employees at PT Matahari Tire Indonesia - Rina Setya Arum; Sri Marhaeni Salsiyah; Suwardi (Politeknik Negeri Semarang, 2025)
This study aims to examine the effect of workplace facilities and cross-cultural communication on the performance of back-office employees at PT Matahari Tire Indonesia. The research background is based on the assumption that limitations in workplace facilities and cultural diversity among employees may influence work effectiveness and performance achievement. This study employed a quantitative approach with a population of 172 back-office employees. The sampling technique used was purposive sampling, by selecting respondents from departments experiencing higher intensity of issues related to workplace facilities and cross-cultural communication compared to other departments, thus considered most relevant to the research focus. Data were collected through questionnaires, interviews, and literature studies, and analyzed using multiple linear regression to determine both simultaneous and partial effects of the independent variables on the dependent variable. The results indicate that workplace facilities and cross-cultural communication have a significant effect on the performance of back-office employees, both jointly and individually. This implies that the better the workplace facilities provided and the more effective the cross-cultural communication among employees, the higher the level of performance achieved. Based on these findings, it is recommended that the company continue to improve the quality of workplace facilities and foster effective cross-cultural communication. In addition, integrating cultural training programs and creating a work environment that supports collaboration across diverse backgrounds are essential to strengthen overall employee performance.